Assessment and Comparison of the Visual Survey Method for Estimating Acorn Production in Holm Oak (Quercus ilex ssp. ballota) Open Woodland of Southwestern Spain - Carevic, Felipe S.; Alejano, Reyes; FERNÁNDEZ, MANUEL; Martín, Daniel (Arid Land Research and Management, 2014)
We assessed the accuracy of a visual survey method for quantification of acorn production in Holm oak in two plots located in the Huelva province of southwestern Spain during three acorn dissemination periods from 2007 to 2010. At the end of September during each period, visual surveys were used to estimate acorn numbers. Four seed traps were placed beneath the crowns of the same trees at the north, south, east, and west positions to determine acorn weight and number on a fortnightly basis during the mast seeding period (October to January). The accuracy of the visual survey was assessed by linear regression and correlation analysis. The results indicated a significant positive correlation of the two methods during all the three time periods. The resulting regression equations allowed estimation of acorn production based on visual surveys. These results suggest that the visual survey method is a simple and precise method that can be used to predict acorn production in Holm oak landscapes.
Keywords: acorn production; mediterranean landscape; visual surveys

Litter production in Holm oak trees subjected to different pruning intensities in Mediterranean dehesas - Andivia, Enrique; VÁZQUEZ-PIQUÉ, JAVIER; FERNÁNDEZ, MANUEL; Alejano, Reyes (Agroforestry systems, 2012)
Litterfall is a key process in forests which is sensitive to climatic conditions like precipitation and temperature, and management practices. Therefore, knowledge about litterfall patterns and its associated variables is important for the conservation of Mediterranean ecosystems under conditions of climate change. We aimed to quantify the temporal pattern of litterfall and to investigate the inﬂuence of abiotic variables and pruning on litter production. Litterfall was collected at monthly intervals for 2 years in trees subjected to different pruning intensities in two locations. The effect of pruning, abiotic variables and tree size on litter production was analyzed using a mathematical model. Leaf fall was strongly seasonal with a peak occurring in the wettest month of the year in this area. The variability in leaf fall was mainly related to rainfall and soil water in 2 years and locations. Pruning reduced the amount of litter production during the ﬁrst year following this practice, and might have negative effect on soil fertility and crop productivity in dehesas ecosystems.
Keywords: á agroforestry systems; á litterfall á; agroforestry systems; climate change; climate change á management; litterfall; management; pruning; Quercus ilex; quercus ilex á pruning

Seasonal evolution of water status after outplanting of two provenances of Holm oak nursery seedlings - Andivia, Enrique; Carevic, Felipe; FERNÁNDEZ, MANUEL; Alejano, Reyes; VÁZQUEZ-PIQUÉ, JAVIER; TAPIAS, RAÚL (New Forests, 2012)
Forest restoration programs using Holm oak (Quercus ilex ssp. ballota [Desf.] Samp.) have had limited success. The effect of plant provenance on plantation success is uncertain, although some previous studies suggest that some provenances may be better able to tolerate stress. We studied the tolerance to drought in seedlings from two Spanish provenances of Holm oak before and after outplanting. One provenance was from a continental climate with cold winters (GR) and the other was from a xeric climate (HU). Seedlings were subjected to a water stress test in the nursery during the summer and survival was visually assessed after 2 weeks. In addition, 35 healthy seedlings of each provenance that were not subjected to the water stress tests were used for outplanting experiment. In these plants the seasonal changes in water potential at dawn (W), speciﬁc leaf area (SLA), cuticular transpiration (Ec ), and loss of xylem hydraulic conductance of twigs (PLC) were measured over 18 months. After the water stress test in summer, mortality was 44.3 % for GR seedlings and 12.6 % for HU seedlings. In addition there were differences between the two provenances in plant water status after planting. The HU provenance had a better water status and was more water conservative in the summer (higher W, lower Ec , lower PLC), but not in the winter. The different drought tolerance and water relations parameters of these two provenances indicate that provenance should be considered in forest restoration and conservation programs involving Holm oak.
Keywords: Adaptation; Drought; Field performance; Physiological traits; water stress

Two provenances of Quercus ilex ssp. ballota (Desf) Samp. nursery seedlings have different response to frost tolerance and autumn fertilization - Andivia, Enrique; FERNÁNDEZ, MANUEL; VÁZQUEZ-PIQUÉ, JAVIER; Alejano, Reyes (European Journal of Forest Research, 2011)
Despite evidences that Holm oak has a high plasticity and great adaptability, there is limited or contradictory knowledge of the morphological and physiological variability of this species. Holm oak has been widely used for reforestation projects in Mediterranean areas, but has frequently shown poor ﬁeld performance. We hypothesized that Holm oak has inter-population differences in physiological responses to abiotic stressors that could affect reforestation success. The inﬂuence of nursery culture on the characteristics of Holm oaks from different provenances has not been explored in depth. Thus, we studied the effect of nursery autumn fertilization on morphological traits, frost tolerance, root growth potential, and nutritional status of two Spanish provenances of Holm oak, La Alcarria (a region with inland Mediterranean climate) and Sierra Morena Occidental (a region with a warm coastal Mediterranean climate). There were signiﬁcant differences between the provenances in frost tolerance, biomass allocation, and leaf nutrient content, suggesting a role of genetic factors. The leaves of seedlings from La Alcarria had less visual damage at -12C than seedlings from the warmer provenance (45% vs. 92%). Seedlings from La Alcarria, compared to those from Sierra Morena, had higher leaf P concentration (0.17% vs. 0.15%), greater stem diameter (3.1 mm vs. 2.7 mm), lower shoot-to-root dry mass ratio (0.46 vs. 0.53), and lower slenderness (4.03 vs. 5.31). For both provenances, N autumn fertilization improved growth, root growth potential, cold hardiness, and nutritional status of seedlings. We suggest that forest reforestation programs should consider to a greater extent Holm oak provenances and their tolerances to different abiotic stressors.
Keywords: á autumn fertilization; á reforestation á; Adaptation; adaptation á cold hardiness; Autumn fertilization; Cold hardiness; Holm oak; holm oak á provenance; provenance; Reforestation